Cryptotanshinone Inhibits the Growth of HCT116 Colorectal Cancer Cells Through Endoplasmic Reticulum Stress-Mediated Autophagy - Fu, Xiaojing; Zhao, Wenwen; Li, Kangkang; Zhou, Jingyi; Chen, Xuehong (Frontiers in Pharmacology, 2021)
Colorectal cancer (CRC) has the highest annual incidence and death rate in the world. Considering severe adverse reactions of chemotherapy medications, traditional Chinese medicines have become potential therapy drug. In our study, the effect of cryptotanshinone (CPT), a major component of Salvia miltiorrhiza Bunge (Danshen) on CRC and related mechanism were explored. Firstly, data from in vitro experiments and zebrafish models showed that CPT selectively inhibited the growth and proliferation of HCT116 and SW620 cells while had little effect on SW480 cells. Then, both ER stress and autophagy were proved participated in regulating CRC viability. Interestingly, ER stress inhibitor and autophagy inhibitor merely alleviated HCT116 cells damage in response to CPT stimulation while have little effect on SW620 cells. The significance of apoptosis, autophagy and ER stress were verified by clinical data from CRC patients. Collectively, the present study has revealed the anti-cancer roles of CPT in CRC by activating autophagy signaling mediated by ER stress. CPT is a promising therapeutic target for CRC treatment.